2015
DOI: 10.1021/acs.nanolett.5b00744
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-like Silicon Nanowires-Based Three-Dimensional Anodes for High-Capacity Lithium Ion Batteries

Abstract: Here, we report on the scalable synthesis and characterization of novel architecture three-dimensional (3D) high-capacity amorphous silicon nanowires (SiNWs)-based anodes with focus on studying their electrochemical degradation mechanisms. We achieved an unprecedented combination of remarkable performance characteristics, high loadings of 3-15 mAh/cm(2), a very low irreversible capacity (10% for the 3-4 mAh/cm(2) anodes), current efficiency greater than 99.5%, cycle stability (both in half cells and a LiFePO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 30 publications
3
85
0
Order By: Relevance
“…. Comparable SiNW loadings on carbon meshes have been recently reported by Peled et al 21. using commercially available Au nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…. Comparable SiNW loadings on carbon meshes have been recently reported by Peled et al 21. using commercially available Au nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
“…Recently, SiNW/C composite negative electrodes with comparable capacity have been reported for LiFePO 4 2 nd Generation batteries21. In this work, prelithiated SiNW/C composite electrodes have been integrated in high capacity Li/S batteries to replace Li metal as only negative electrode with sufficient capacity.…”
Section: Resultsmentioning
confidence: 99%
“…151 In addition, it was found that all measured SEI parameters for the 3D SiNW anode -R SEI , ρ SEI and SEI thickness -grow with cycle number. However, the growth of the secondary porous SEI was much higher than the growth of the compact SEI (measured by EIS).…”
mentioning
confidence: 97%
“…[97] The VLS method is usually carried out in the chemical vapor deposition (CVD) reactor by using silicon-containing gas as silicon sources, such as silane (SiH 4 ) or tetrachloride (SiCl 4 ), and the reaction temperature varies from 300 to 1000 C depending on the gas precursor and different kinds of metal catalysts utilized in the fabrication process. [98,99] In 2007, Chan et al presented a direct growth of Si NWs on the stainless-steel current collector by VLS synthesis method with Au as catalyst. [39] When tested as an anode material, an extremely high reversible capacity of 3124 mAh g À1 at a current density of 0.05 C was obtained in the first charge process and the initial Coulombic efficiency was 73%.…”
Section: Nanowiresmentioning
confidence: 99%